Implementasi Pendidikan Karakter Lokal Kasundaan Berbasis Kebijakan SPBS di Kabupaten Sumedang Jawa Barat - Nurjaman, Omay Komara; Julia, Julia (Universitas Pendidikan Indonesia, 2018)
This study aims to analyze the implementation of policy on kasundaan character education based on Sumedang Regent regulation about Sumedang Puseur Budaya Sunda (SPBS). The method used was a survey to the elementary school students, which was completed with interviews and FGD. The results of the study found that: (1) SPBS was only instructed in the